EDITORIAL NOTE - Abdul Kadir Othman (Asian Academy of Management Journal, 2019)
It is our pleasure to contribute to the creation and dissemination of knowledge in Islamic Management as stipulated in the main objective the establishment of World Academy of Islamic Management (WAIM). From WAIM’s first academic conference, which was held in Universiti Kuala Lumpur (UniKL), Malaysia in April 2018, several papers were published in selected Scopus-indexed journals. Asian Academy of Management Journal (AAMJ) is one of the journals that has allocated its space for nine outstanding articles to be published in its second special issue in October 2019. The first paper entitled “Measuring the Effects of Work Motivation on Stress and Performance Linkages in SME” was written by Sheikh Muhamad Hizam Sheikh Khairuddin, Zulkifli Saidun, and Muhamad Shahrin Hashim. The paper is concerning the approach that can be used to manage stress and improve performance of employees working in small and medium-sized enterprises (SMEs). The second paper was written by Ismila Che Ishak, Mohamad Fitri Azlan, Shaiful Bakri Ismail, and Norhayati Mohd Zainee. As reflected in its title, “A Study of Human Error Factors on Maritime Accident Rates in Maritime Industry,” the paper highlights the most critical human factors that contribute to maritime accident rates. The third paper was written by Akmal Latiff Ayob, and Norzanah Mat Nor with the title, “Predictors of Employee Engagement in Malaysia, and the Moderating Effects of Job Demands and Total Reward.” The paper contributes to the enhancement of employee engagement through job demand and reward. The fourth paper was collectively written by Khatijah Othman, Siti Nurbaya Ismail, Shahrul Hafifi Mohd Fuad, Masni Md Hasim, Fadhilah Othman, Muhammad Rahmat Abdullah, Norwini Zaidi, Nur Adlina Addenan, and Nik Nadian Nisa Nik Nazli. It highlights the role of service period in enhancing the relationship between behaviour and work performance. The fifth paper was by Ahmad Amri Zainal Adnan, Nek Kamal Yeop Yunus, and Arsalan Mujahid Ghouri entitled, “Does Religiosity Matter in the Era of Industrial Revolution 4.0?” The authors have brilliantly discussed the role of religiosity in this new era of the “Internet-based of things.” The sixth paper was about establishing the “Model for Turnover Intention: Banking Industry in Malaysia,” which was written by Mohammad Falahat, Gee Siew Kit, and Liew Chin Min. It is expected that this model would help reduce the turnover rate in banking sector. The seventh paper was written by Mohammad Falahat, Yan-Yin Lee, Yi-Cheng Foo, and Chee-En Chia. Its title is “A Model for Consumer Trust in E-Commerce” that is expected to add value to the existing body of knowledge on e-commerce. The eighth paper was written by Nazatul Shima Abdul Rani, K. Sarojani Krishnan, Zurinah Suradi, and Nurita Juhdi. Its title, “Identification of Critical Components of Resilience During and After Economic Crises: The Case of Women Food Operators in Kuala Lumpur” is meant to identify factors that contribute to survival of women food operators during economic crisis. The ninth paper was written by Gholam Reza Zandi, and Nur Amalina binti Abdullah entitled, “Financial Statements Timeliness: The Case of Malaysian Listed Industrial Product Companies”. It is meant to highlight the importance of ensuring the timeliness of the financial statement in ensuring a firm’s performance. In conclusion, we acknowledge all our editors, members of the editorial board and reviewers for their continued support and encouragement. We are highly confident that this issue will bring WAIM closer to achieving its mission to create and disseminate knowledge in Islamic Management.